(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
The article tries to interrogate the poetic-topographical processes in the performing arts from the spatial paradigms established by transgender bodies in the recent Brazilian scene. The reflection puts in tension the phenomena of space performativity (Mostaço, 2016) and transgender performativity (Leal, 2018b), seeking to understand gender habitat traits in contemporary arts. The transvestite spatiality is then thought from provocative scenic configurations raised by attitudinal modes of protection and creation of gender in the environment. In this sense, from the incitement of recent creative processes, and the notion of environmental racism (Santos et al., 2016), we analyze the categories of passability, confinement and cisplay as possible modes of environmental violence to transgenderities.